(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
In modern Indian political discourse the custom of dowry is often represented as the cause of serious social problems, including the neglect of daughters, sex-selective abortion, female infanticide, and the harassment, abuse, and murder of brides. Attempts to deal with these problems through legislative prohibition of dowry, however, have resulted in virtually no diminution of either dowry or violence against women. In contrast, radically different interpretations of dowry can be found in the literatures of structural- functionalist anthropology, economics, and human behavioral ecology which muster wide-ranging forms of qualitative and quantitative evidence to support functional models of dowry as a form of inheritance or investment in daughters and/or their children. This study argues that a functionalist perspective on dowry could lead to improved dowry policy, and that an approach based in human behavioral ecology (HBE) is uniquely suited to this task. After reviewing the relevant literature on dowry in South Asia, I discuss current dowry legislation and its limitations.